THE INFLUENCE OF CONSUMER BEHAVIOR TOWARDS ORIFLAME PRODUCTS AT PT ORINDO SURABAYA BRANCH - Zainal Fanani; Achmad Efendi; Agus Sanjaya (International Journal of Economics, Science, and Education, 2024)
This study aims to describe the analysis of consumer behavior towards Oriflime products at PT Orindo Alam Ayu Surabaya branch. The data studied were reports of social factors, personal factors, and psychological factors. The company has an Oriflime sales network supported by millions of consultants who introduce products to consumers directly. The problem in this study is to assess consumer behavior from various social, factors, personal factors, and psychological factors. This method of research uses a descriptive quantitative method using techniques for harvesting dispersal data or questionnaires.